Quantitative analysis of dyssynchrony assessed by multidetector computed tomography can predict clinical outcome after cardiac resynchronization therapy. (25th November 2020) - Onishi, T; Koyama, Y; Inoue, K; Okamura, A; Iwamoto, M; Tanaka, K; Nagai, H; Hirao, Y; Oka, T; Tanaka, N; Watanabe, S; Sumiyoshi, A; et al.
Abstract: Background: The degree of mechanical dyssynchrony has been suggested as a predictor for long-term survival after cardiac resynchronization therapy (CRT). There have been little reports of dyssynchrony assessment with the use of cardiac computed tomography (CCT). Methods: We studied 35 heart failure (HF) patients (average age 67±10 years) referred for CRT with NYHA III-IV heart failure, left ventricular (LV) ejection fraction (EF) 20±10% (all ≤35%), and QRS duration 156±22 ms (all ≥120ms). Electrocardiogram-gated contrast-enhanced 256-slice multidetector CT was performed before CRT. Based on CCT, the LV endocardial boundaries from short-axis images reconstructed at 5% increments of cardiac cycle were automatically detected, and the time from R-wave to maximal wall motion was calculated for each of the 16 standardized segments for all slices using software "Myocardial Contraction Map". The standard deviation modified by mean heart rate (%SD) was respectively calculated as the global parameter of dyssynchrony. LVEF was also measured using MDCT. The predefined primary end-point was the first HF hospitalization or death over 2 years. Results: %SD was feasible in all patients, respectably. There were 16 events over 2 years; 11 HF hospitalizations and 5 deaths. Patients with %SD ≥22% (optimal cutoff for outcome by ROC curve analysis) had a better clinical outcome than patients with %SD <22% (p=0.01, Figure). Conclusion: Patients who had %SD ≥22% assessed by MDCT had a particularly favorable event-free survival following CRT, and this appears to be an important prognostic marker. Funding Acknowledgement: Type of funding source: None